2014
DOI: 10.1158/1541-7786.mcr-13-0604
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Kinase PI4KIIIβ Is Highly Expressed in Breast Tumors and Activates Akt in Cooperation with Rab11a

Abstract: Emerging evidence now implicates phosphatidylinositol 4-kinases (PI4K), enzymes that generate PI(4)P from phosphatidylinositol (PtdIns), in cancer. In this study, we investigate the role of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 65 publications
0
43
0
Order By: Relevance
“…In summary, we have identified an import role for PI4KIIIβ in cell shape, migration and adhesion. PI4KIIIΒ is likely to be a human oncogene (Waugh, 2012;Morrow et al, 2014) and we propose that its role in cancer is related to its regulation of these processes. In the further it will be important to identify the cargo involved.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In summary, we have identified an import role for PI4KIIIβ in cell shape, migration and adhesion. PI4KIIIΒ is likely to be a human oncogene (Waugh, 2012;Morrow et al, 2014) and we propose that its role in cancer is related to its regulation of these processes. In the further it will be important to identify the cargo involved.…”
Section: Discussionmentioning
confidence: 93%
“…The best known function of PI4KIIIβ is the generation of PI4P from PI (Balla and Balla, 2006;Balla, 2013). In addition, PI4KIIIβ binds to the Rab11a GTPase in a kinase-independent fashion (de Graaf et al, 2004;Polevoy et al, 2009;Burke et al, 2014) and is be involved in Rab11a-dependent control of Akt signaling (Jeganathan et al, 2008;Morrow et al, 2014) and endosome function (de Graaf et al, 2004;Polevoy et al, 2009). In our case, a catalytically inactive version of PI4KIIIβ rescues neither the reduced migration nor cell shape changes in PI4KIIIβ-deleted cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with a functional role for PI4KIIIβ in cancer, ectopic PI4KIIIβ expression also disrupts three-dimensional epithelial morphogenesis of breast cells and promotes cell motility and actin remodeling 1,20,31 . Finally, our lab has reported that PI4KIIIβ is able to directly activate Akt signaling 28 .…”
Section: Introductionmentioning
confidence: 95%
“…For example, transcriptional analysis of 1992 primary human breast tumours by Curtis et al identified PI4KB, the gene encoding human PI4KIIIβ, as a cancer driver gene due to its frequent gene amplification and overexpression in primary tumour tissue 7 . Additionally, we have reported that the PI4KIIIβ protein is highly expressed in ~20% of primary human breast tumours 28 .…”
Section: Introductionmentioning
confidence: 99%